“FROM BRICKS TO CLICKS”: RETAIL TECHNOLOGY TRENDS TOWARDS CUSTOMER VALUE CREATION IN ORGANISED CHAINS WITH REFERENCE TO BANGALORE - Satheeshkumar R; Sachana C; Pallavi. S (International Journal of Research -GRANTHAALAYAH, 2025)
This transformation of the bricks to clicks has redesigned the retailing one of the organized apparel markets, has the potential of leading the digital innovation in the retail world. Consumers now strongly require smooth, individualized and immersive shopping experiences, which is causing retailers to implement innovative technologies that include Artificial Intelligence (AI), Internet of Things (IoT), Augmented Reality (AR),Virtual Reality (VR) and interactive digital screens. AI facilitates one-on-one recommendations, trend prediction and chat bot services whereas IoT makes sure that there is real-time stock management via RFID tags and smart shelves. Displaying digital screens offer active advert placements in-store and AR/VR can enable the use of virtual dressing rooms and fully interactive brand environments, connecting the online and offline shop. The tech-friendly growth of Bangalore with its diverse consumer base and equally competitive apparel market creates an interesting set towards examining how well such technologies are being adopted, and how effective. Although there have been heavy investments on such innovations, there is little empirical evidence on the direct effect of the innovations on the customer value creation in the form of satisfaction, engagement, loyalty, trust and purchase confidence. This research paper fills the above-mentioned gap as it examines the perception of customers and the current situation with retailers along with their practices to find out the real potential of retail technologies in organized chains. The emerging concepts will help innovative retailers, technology providers, or policymakers formulate strategies that will not only generate more customer value but also provide sustainable competitiveness in the dynamic retail environment of Bangalore